Survival Outcomes Improved in Contemporary Cohort of Patients With Pelvic or Abdominal Recurrence After Treatment for Stage I/II Endometrial Carcinoma. (December 2017) - Xu, Melody J.; Chu, Christina; Rubin, Stephen; Lin, Lilie L.
Abstract : Objectives: Pelvic and abdominal recurrences in stage I/II endometrial carcinoma are associated with poor outcomes, yet prognostic factors for survival after recurrence are not well described. Herein, we identify patients with pelvic or abdominal recurrence after surgery for stage I/II endometrial carcinoma and describe symptoms at presentation, prognostic factors, and salvage treatment toxicity. Materials and Methods: This is a retrospective cohort of 20 consecutively treated patients with recurrence after treatment for stage I/II endometrial carcinoma followed by our Institution's Radiation Oncology Department from 1998 to 2015. Results: The median time to pelvic or abdominal recurrence was 18.1 months (range, 4.2 to 59.6 mo), with 50% of recurrences at extranodal locations. Two-year progression-free survival (PFS) was 44% and 2-year overall survival (OS) was 82%. Salvage treatments varied widely, including chemotherapy and radiotherapy (RT) (7), surgery and RT (3), and surgery, chemotherapy, and RT (3). On univariate analysis of PFS, symptoms at recurrence ( P =0.04) and extranodal recurrences ( P <0.01) were found to be statistically significant negative prognosticators for PFS. On univariate analysis of OS, increasing age at recurrence and presence of symptoms were found to have a trend toward statistically significant association with negative OS outcomes ( P =0.08 and P =0.10, respectively). Conclusions: Our study demonstrates that long-term survival for pelvic or abdominal recurrences is possible with curative salvage therapy. The presence of symptoms is a negative prognostic factor in treatment outcome, and imaging may be effective for diagnosis in symptomatic and asymptomatic patients. Larger studies need to be performed to confirm these findings.